Kebutuhan Air Tanah di Desa Rawan Kekeringan Kecamatan Sempor Kabupaten Kebumen - Islammei, Rahayu Annisa; Wahyu, Setyaningsih (Geo-Image, 2019)
Society use groundwater sources to meet water needs. The water sources used are springs and wells. In the dry season the water source decreases, water needs of the society cannot be fulfilled by the availability of groundwater. The aims of this study are to know the water needs of the society in villages which prone to drought in Sempor subdistrict.Domestic water needs of villages which prone to drought in Sempor subdistrict are 1,063,313 liters/day.